Conscientious Objection in an Uncertain Time: New Challenges in Ireland - Ryan, Desmond (Religions, 2023)
This paper explores the legal framework concerning the conscientious objection rights of employees in Ireland and critically considers how the various sources within that legal framework may overlap and intersect. It specifically considers the uncertainties created by section 22 of the Health (Regulation of Termination of Pregnancy) Act 2018 and its interaction with the Constitution of Ireland, the common law, other statutory regimes in employment law, EU law and the European Convention on Human Rights. In conducting this analysis, the paper attempts to map out likely future directions of travel within the law of conscientious objection in the context of termination of pregnancy in Ireland.